INFLUENCE OF LIFESTYLE FACTORS ON AGNI AMONG YOUNG ADULT A PILOT STUDY - PRATIMA GUPTA; VAIDEHI VINAY RAOLE (The Bioscan, 2025)
Agni, the fire element in the body, is responsible for the conversion of food into energy, essential for all vital functions. If Agni ceases to function, death occurs, making its maintenance critical for health. There are three types of Agni: jatharagni (digestive fire), bhootaagni (chemical fire), and dhatwagni (metabolic fire). Among these, jatharagni plays the most significant role in maintaining health, with four functional states: vishamagni (irregular), teekshnagni (intense), mandagni (low), and samaagni (normal). Samaagni, the balanced state, is crucial for maintaining health. This paper explores the relationship between Agni and lifestyle diseases, emphasizing the importance of maintaining a balanced Agni for health. Material & Methods: A cross-sectional survey was conducted among 100 healthy individuals of the 18 to 30 years age group of either gender. Jatharagni was assessed by using a standardized questionnaire. Result: Association of Agni with the lifestyle was done by using principal component analysis and correlation method. A statistically significant correlation was established at the level of p < 0.01. Conclusion: Though the result showed significant association, large population-based works are needed for conclusional statements.